Investigating the Impact of Various Abutment Materials on Peri-Implant Tissue Health at Tripoli-Libya - Khalid Omar; Salma Zariba; Ghada Alzwaghi (AlQalam Journal of Medical and Applied Sciences, 2024)
This research investigates the impact of different abutment materials, including titanium, zirconia, and hybrid materials, on peri-implant tissue health in dental implantology. A prospective cohort study design was employed, involving 150 participants who received single or multiple dental implants from Banzi & Bianco s.r.l. (B&B) a dental implant company based in Italy. Clinical parameters, such as peri-implant probing depth, bleeding on probing, and radiographic analysis, were measured at baseline and at 3-, 6-, and 12-months post-abutment placement. Statistical analyses, including ANOVA and regression, were conducted to identify significant associations between abutment materials and peri-implant tissue health parameters. The results revealed nuanced relationships among the abutment materials and their impact on peri-implant tissue health. Interestingly, the hybrid material group exhibited more favorable outcomes in maintaining optimal tissue health compared to the titanium and zirconia groups. This finding suggests that the choice of abutment material can significantly influence the long-term health of peri-implant tissues. This study contributes valuable insights for clinicians in selecting abutment materials for dental implant restorations, highlighting the importance of considering hybrid materials as a potential option for better clinical outcomes (p< 0.001). يبحث هذا البحث في تأثير المواد الداعمة المختلفة، بما في ذلك التيتانيوم والزركونيا والمواد الهجينة، على صحة الأنسجة المحيطة بالزرعة في زراعة الأسنان. تم استخدام تصميم دراسة أترابية مستقبلية، شملت 150 مشاركًا تلقوا زراعة أسنان فردية أو متعددة من شركة Banzi&Bianco s.r.l. شركة زراعة أسنان مقرها في إيطاليا. تم قياس المعلمات السريرية، مثل عمق الفحص حول الزرع، والنزيف عند الفحص، والتحليل الشعاعي، عند خط الأساس وفي 3 و6 و12 شهرًا بعد وضع الدعامة. تم إجراء التحليلات الإحصائية، بما في ذلك تحليل التباين (ANOVA) والانحدار، لتحديد الارتباطات المهمة بين المواد الداعمة ومعايير صحة الأنسجة المحيطة بالزرعة. كشفت النتائج عن وجود علاقات دقيقة بين مواد الدعامة وتأثيرها على صحة الأنسجة المحيطة بالزرعة. ومن المثير للاهتمام أن مجموعة المواد الهجينة أظهرت نتائج أكثر إيجابية في الحفاظ على صحة الأنسجة المثلى مقارنة بمجموعتي التيتانيوم والزركونيا. تشير هذه النتيجة إلى أن اختيار مادة الدعامة يمكن أن يؤثر بشكل كبير على صحة الأنسجة المحيطة بالزرعة على المدى الطويل. تساهم هذه الدراسة برؤى قيمة للأطباء في اختيار المواد الداعمة لترميم زراعة الأسنان، مع تسليط الضوء على أهمية النظر في المواد الهجينة كخيار محتمل لتحقيق نتائج سريرية أفضل